Hubungan antara Kejadian Tuberkulosis Ekstra Paru dengan Kadar Limfosit dan Monosit di RSUD Dr. H. Abdul Moeloek Provinsi Lampung periode Januari 2018-Desember 2019 - Raihanah Nabilah; Putu Ristyaning Ayu Sangging; Anggraeni Janar Wulan (CV. Jasa Sukses Abadi, 2023)
Extra pulmonary tuberculosis (extra pulmonary TB) is a TB infection that attacks organs other than the lungs and is also a complication of TB. Adaptive immune response plays an important role in TB patients, one of which is the role of lymphocytes as antigen-antibody specificity and monocytes as phagocytosis of pathogens. The aim of this study was to determine the relationship between the incidence of extrapulmonary TB patients with lymphocyte and monocyte levels in RSUD dr. H. Abdul Moeloek Lampung Province. This research is a type of retrospective analytic observational study with a cross-sectional research design which was conducted in December 2020 levels in RSUD dr. H. Abdul Moeloek Lampung Province by looking at medical records for the period January 2018-December 2019. The sampling technique was consecutive sampling and calculated using the Slovin formula with a total sample of 103 patients. The analysis used is the chi square test. Central nervous system TB patients totaled 80 people who had lymphocytopenia 66 people (82.5%) and normal lymphocytes 14 people (17.5%), in TB lymphocytopenic patients there were 23 people who had lymphocytopenia 14 people (60.9%) and normal lymphocytes 9 people (39.1%). As for monocyte levels, there were 80 central nervous system TB patients with normal monocytes 50 people (62.5%) and monocytosis as many as 30 people (37.5%), in TB lymphadenitis patients there were 23 people with normal monocytes 12 people (52 .2%) and monocytosis in 11 people (47.8%). The results of the chi square test on lymphocyte levels with a value of p = 0.028 and monocyte levels with a value of p = 0.373, which means that there is a relationship between the incidence of extra pulmonary TB and lymphocyte levels and there is no relationship between the incidence of extra pulmonary TB and monocyte levels levels in RSUD dr. H. Abdul Moeloek Lampung Province.